Relations of blood? Racialization of civic identity in twenty-first century Hong Kong. Issue 6 (2nd November 2019) - Jackson, Liz
ABSTRACT: This paper explores how notions of race, ethnicity, and blood are mobilized in educational texts in Hong Kong. It elaborates how civic identity is racialized as part of a nationalist education operating beneath the surface of expressed commitments to global citizenship, human rights, etc., in curriculum and textbooks. Many have commented on how cultural and ethnic ties are prioritized over political principles as bases for civic education in Asian societies. These cultural/ethnic bases should be critically examined, however, as they imply racial/ethnic exclusions. Examining how race, ethnicity, and blood are used to justify cultural framings of civic identity leads to questions about how education can be used to unify some, while alienating others from a sense of belonging and community. I argue that racialization of Hong Kong civic identity is not a happy solution for all members of society, and for more inclusive visions of identity in education.